2003
DOI: 10.1128/mcb.23.24.9150-9161.2003
|View full text |Cite
|
Sign up to set email alerts
|

Generation and Analysis of Siah2 Mutant Mice

Abstract: Siah proteins function as E3 ubiquitin ligase enzymes to target the degradation of diverse protein substrates. To characterize the physiological roles of Siah2, we have generated and analyzed Siah2 mutant mice. In contrast to Siah1a knockout mice, which are growth retarded and exhibit defects in spermatogenesis, Siah2 mutant mice are fertile and largely phenotypically normal. While previous studies implicate Siah2 in the regulation of TRAF2, Vav1, OBF-1, and DCC, we find that a variety of responses mediated by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
73
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(73 citation statements)
references
References 61 publications
0
73
0
Order By: Relevance
“…The generation of double knockout animals for the mouse homo- logues of Siah, Siah1a and Siah2, has demonstrated an essential role in embryonic development, whereas the individual knockout phenotypes are less severe (25)(26)(27)(28). Currently, little is known about the regulation of Siah, but it appears that hypoxia, Wnt 5a, and p53 are capable of up-regulating Siah mRNA and protein expression (28)(29)(30).…”
Section: Discussionmentioning
confidence: 99%
“…The generation of double knockout animals for the mouse homo- logues of Siah, Siah1a and Siah2, has demonstrated an essential role in embryonic development, whereas the individual knockout phenotypes are less severe (25)(26)(27)(28). Currently, little is known about the regulation of Siah, but it appears that hypoxia, Wnt 5a, and p53 are capable of up-regulating Siah mRNA and protein expression (28)(29)(30).…”
Section: Discussionmentioning
confidence: 99%
“…PyMT-Siah2 À/À and PyMT-WT mice were generated by crossing C57Bl/6 Siah2 À/À mice (20) with C57Bl/6 PyMTtransgenic mice (kindly provided by Carol MacLeod and Lionel Hebbard, University of California, San Diego, San Diego, CA). All procedures involving mice were conducted in accordance with NHMRC regulations on the use and care of experimental animals and were approved by the Peter MacCallum Cancer Centre Animal Ethics Committee.…”
Section: Animalsmentioning
confidence: 99%
“…Other investigators have reported that the E3 ligase activity of TRAF2 regulates TNF-␣-mediated activation of both NF-B and JNK through ubiquitination of RIP1 and JNK. 40,41,[43][44][45] Although we found that TRAF2 co-precipitates with JAB1, we were unable to demonstrate co-precipitation of RIP1 with JAB1 using a tech- were cultured for 48 hours and lysed using immunoprecipitation lysate buffer (Roche). Aliquots of 1 mg of the total protein lysates were immunoprecipitated with a polyclonal anti-Jab1 antibody.…”
Section: Discussionmentioning
confidence: 97%